Contact Strength Analysis of Azimuth Gear Transmission System of Two-axis Tracking Device - Li Shiqing; Peng Youduo; Chen Yu (Jixie chuandong)
A built-in solar azimuth tracking device is designed. Then,its 3D model of azimuth angle gear transmission system is established by using UG,the wind load and boundary conditions are determined.The finite element analysis of the gear transmission system is carried out based on the ANSYS Workbench simulation environment. Finally,the integral stress distribution condition and other important properties of the gear transmission system are obtained and verified by using the Hertz theory. The results show that the maximum stress of gear transmission system is 408. 29 MPa by finite element analysis and appear in the idler gear meshing,near the dedendum transition curve is obvious exist stress concentration,and the stress fluctuation on worm and gear is bigger. The contact strength of the tooth surface is analyzed and calculated by using the Hertz theory. The results are verified by the finite element method. This study can provide a certain reference and basis for the gear design and dynamic analysis of gear transmission system of two-axis tracking mechanism.